Estudo da degradação de blendas de polipropileno com aditivos comerciais - Pires, Jéssica Pereira (2019)
Polypropylene (PP) has been widely used by industry, especially in the packaging sector, so it is important to develop research related to its biodegradability to minimize the effects of its disposal in the environment. The objective of this work is to evaluate the degradation of polypropylene as well as the biodegradation of PP through the incorporation of two different additives, Pepzyme and Eco-One. To this end, PP blends were produced with different percentages of additives, which have the purpose of conferring biodegradability to the material, since the polypropylene presents high resistance to degradation. In order to verify the behavior of the materials against degradation tests with 3 different media (soil, salt water and fresh water) for a period of 6 months, the samples were characterized by Differential Scanning Calorimetry, Infrared Spectroscopy with Fourier Transform, Thermogravimetric Analysis and Scanning Electron Microscopy with Field Emission. The characterization was carried out in order to verify the changes in the structural characteristics, the morphology and thermal properties of the materials caused by the incorporation of the additive and the exposure to the degradation media. From the obtained results it was observed that the additives influenced the degradation of PP. In addition, the Eco-One additive and the saline medium caused more significant changes in the analyzed properties, indicating a greater influence on the degradation process. It was concluded that the incorporation of the commercial additives attributes to the PP biodegradant properties. In this way, this work has an important role in the research and development of biodegradable materials with the aim of minimizing the effects caused by plastic waste in the environment.